2021
DOI: 10.3389/fphar.2021.630210
|View full text |Cite
|
Sign up to set email alerts
|

Jian-Pi-Yi-Shen Formula Ameliorates Oxidative Stress, Inflammation, and Apoptosis by Activating the Nrf2 Signaling in 5/6 Nephrectomized Rats

Abstract: Chronic kidney disease (CKD) is an increasing global public health problem, with high morbidity and mortality. Jian-Pi-Yi-Shen (JPYS) formula is a representative traditional Chinese medicine formula in the treatment of CKD, which is widely used in clinical practice in China. However, the underlying mechanism has not been well elucidated. In the present study, we measured the markers of apoptosis, inflammation, oxidative stress, and nuclear factor erythroid 2–related factor 2 (Nrf2) signaling to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A large number of studies have shown that traditional Chinese medicine and its active ingredients can effectively promote the remission of kidney disease. 18 , 19 Kidney is an important target organ for iohexol-induced cytotoxicity. Iohexol-induced AKI involves multiple pathophysiological mechanisms, including renal inflammation, pyroptosis, oxidative stress, proximal renal tubular injury, and vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that traditional Chinese medicine and its active ingredients can effectively promote the remission of kidney disease. 18 , 19 Kidney is an important target organ for iohexol-induced cytotoxicity. Iohexol-induced AKI involves multiple pathophysiological mechanisms, including renal inflammation, pyroptosis, oxidative stress, proximal renal tubular injury, and vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the 5/6 nephrectomy model has been recognized as the classical model most similar to human CKD. It has been widely used to study the therapeutic effect of drugs on CKD ( Mizukami et al, 2019 ; López-Baltanás et al, 2021 ; Zhou et al, 2021 ). Moreover, the 5/6 nephrectomy model also show significant gut microbiota dysbiosis ( Liu et al, 2018 ; Feng et al, 2019 ), and this model may be suitable in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the studies of TCMs have attracted attention owing to its superiority in the treatment of refractory diseases ( Chen et al, 2016b ; Li et al, 2021a ; Shao G. et al, 2021 ; Wang Y. W. et al, 2021 ; Yang and Wu, 2021 ). A variety of compounds isolated from natural products have been protected against renal fibrosis ( Feng et al, 2019b ; Luo et al, 2021 ; Shao M. et al, 2021 ; Zhao et al, 2011 ; Zhou F. et al, 2021 ). Therefore, natural products have attracted more and more attention around the world and are committed to the development of new drugs.…”
Section: Natural Products As An Alternative Therapy Against Tubuloint...mentioning
confidence: 99%